On the identity of Prochyliza nigrimana (Meigen) and Prochyliza nigricornis (Meigen) (Diptera: Piophilidae), with a synopsis of Prochyliza Walker and description of a new species - Martín-Vega, Daniel (Zootaxa, 2014)
With representatives distributed throughout the Holarctic and Neotropical regions, the genus Prochyliza Walker (Diptera: Piophilidae) is known from eight species. There has been, however, considerable controversy over the identity of two of them: the common, synanthropic species Prochyliza nigrimana (Meigen), and the rarely collected Prochyliza nigricornis (Meigen). The described differences between both species were only based on body colouration but, since a wide colour variation has been documented among P. nigrimana individuals, several authors had suggested that both taxa might be just extreme colour variants of the same species. Recent collections from central Spain showed that the colouration characters described for P. nigricornis certainly apply to dark P. nigrimana individuals, but also to other Prochyliza specimens showing distinct morphological characters and genitalia. In order to solve this controversy, the holotypes of both P. nigrimana and P. nigricornis were studied, concluding that both specimens are conspecific and instating P. nigricornis as a subjective junior synonym (syn. nov.). A new species, Prochyliza georgekaplani sp. nov., is described from specimens collected in central Spain. A synopsis and an updated identification key to the known species of the genus Prochyliza are also provided.